COPING STRES MAHASISWI TINGKAT AKHIR PROGRAM STUDI PSIKOLOGI UNIVERSITAS SAHID SURAKARTA - Aqvina Rahma Diyanti (JURNAL TALENTA PSIKOLOGI, 2026)
Stress can be experienced by final year female students due to the pressure of completing their final assignments, accompanied by various obstacles. This condition makes stress coping an important skill in dealing with the stress experienced. The purpose of this study was to provide an overview of stress coping among final year female students in the Psychology Study Program at Sahid University Surakarta. The method used was qualitative research involving five main informants and two supporting informants. The results of the study show that female students have fairly good stress coping skills. They are able to overcome problems they face both externally and internally, and are able to strengthen themselves against the pressures of the final semester. Stress coping is important for final-year female students. With stress coping, female students can control the pressure they feel so that they can complete their final assignments well.